AN ANALYSIS OF SILK ROUTE AS A CONDUIT OF CULTURE AND COMMERCE IN POST-MAURYAN INDIA - Kumar, Amol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Silk Route, renowned for connecting the East and the West, served as a vital channel for trade and cultural exchange between ancient civilizations. During the Post-Mauryan period in India (approximately 2nd century BCE to 3rd century CE), the significance of this transcontinental network expanded substantially. This research undertakes a comprehensive analysis of how the Silk Route functioned as both an economic lifeline and a cultural bridge during this transformative phase of Indian history. Following the decline of the Mauryan Empire, various regional powers such as the Indo-Greeks, Shakas, Kushanas, and Satavahanas emerged, each playing a crucial role in facilitating long-distance trade and cultural diplomacy. These polities not only encouraged commercial activity by securing trade routes and minting coinage but also acted as patrons of art, religion, and architecture that were influenced by and contributed to broader Silk Route exchanges. Commodities like silk, spices, ivory, textiles, and precious stones were exported from India, while imports included gold, horses, glassware, and fine ceramics from Central Asia, China, and the Mediterranean world.Beyond the exchange of goods, the Silk Route enabled the transmission of religious ideas—most notably Buddhism. The movement of Buddhist monks, pilgrims, and texts along these routes contributed to the spread of Indian philosophical and spiritual thought to regions such as Central Asia, China, and beyond. Artistic styles such as Gandhara and Mathura reflect a unique syncretism born from Indo-Greek and Central Asian influences, showcasing how trade catalyzed cultural fusion. This study draws upon archaeological findings, inscriptions, literary sources, and numismatic evidence to present a holistic picture of the era. It highlights the Silk Route’s role in transforming India into a cultural and economic powerhouse, linking it intricately with global historical processes. The paper argues that Post-Mauryan India’s participation in the Silk Route laid foundational stones for early globalization, making it a key contributor to the ancient world economy and intercultural dialogue.